Effect of Natural Zeolite Powder on Physical and Mechanical Properties of PP-g-MA Particle Boards and Divinylbenzene Using Palm Oil Stem Powder with Soaking Chloroacetic Acid 3% - Yugia Muis; Een Melani Harahap (Journal of Chemical Natural Resources, 2022)
The effect of natural zeolite stem on physical and mechanical properties of particle boards from PP-g-MA and divinylbenzene with palm stem oil has been conducted soaked with 3% chloroacetic acid. It was performed in three steps. The first was soaking palm oil trunk in 3% chloroacetic acid for 24 hours, then filtering and rinsing until neutral. The second was polypropylene functionalization with maleic anhydride to form PP-gM A with the reflux method. PP-g-MA degree of grafting, melting point, and FT-IR analysis analyzed MA. The degree of grafting maleic anhydride of polypropylene was 9 .467 %, 1 62.06 o C melting point used for particle board adhesive. The third was particle board manufacture consisting of palm oil trunk, polypropylene, PP-g-MA, benzoyl peroxide, divinyl benzene, and zeolite with ratios of (7 0: 4 0: 3 0:2: 3: 0)g, (70: 4 0: 3 0:2:3 :3 )g, (70: 4 0: 3 0:2: 3: 6) g, (70: 4 0: 3 0:2: 3: 9 ) g, (70: 4 0: 3 0:2: 3: 12) g and (70: 4 0: 3 0:2: 3: 15) g as specimens I, II, III, IV, V, VI respectively. Physical and mechanical analysis for particle boards based on SNI 03-2105-2006 includes density, water content, swelling, modulus of rupture, and modulus of elasticity. SEM was used to analyze broken fragments of boards. From the characterizations obtained, specimen I V was the best result. All of the physical properties' values matched with particle board quality standard, with the value of MoE being 32438.53 KgF/cm2. The value of MoR was 86.50 KgF/cm2; SEM analysis showed an effect of zeolite on particle boards.